Inferno : the fiery destruction of Hamburg, 1943 - Lowe, Keith 1970- (Scribner, 2007)
In the summer of 1943, British and American bombers launched an attack on the German city of Hamburg unlike anything the world had ever seen. For ten days they pounded the city with over 9,000 tons of bombs. The firestorm they created was visible for 200 miles, and pockets burned for a month. The people of Hamburg had no time to understand what had hit them. As they emerged from their cellars and shelters, they were confronted with a vision of hell: a sea of flame, the burned-out husks of fire engines, roads that had become flaming rivers of melted tarmac, and hurricane-force winds. Writer Lowe interviewed eyewitnesses and gathered together hundreds of documents. His book gives the human side of an inhuman story: the long, tense buildup to the Allied attack; the unparalleled horror of the firestorm itself; and the terrible aftermath.--From publisher description